PEMBERDAYAAN GURU UNTUK PENINGKATAN KETERAMPILAN MENYUSUN MODUL AJAR MENGGUNAKAN MODUL AJAR GENERATOR - Krismiyati, Krismiyati; Yulia, Hanita; Dwi Kurnaningsih, Yari (LPPM Universitas Bina Bangsa, 2024)
Designing lessons is an integral part of teacher practice. With the implementation of the national curriculum based on the emancipated curriculum, teachers are given the freedom to develop learning tools according to the needs and characteristics of students in their respective schools. However, in reality, it is more challenging than imagined in the field. Teachers still need help in developing teaching modules independently. Therefore, this community service activity aims to empower teachers using technology in the form of a module generator application that can assist teachers in developing learning tools in the form of teaching modules according to the subjects they teach. This PkM activity is carried out in 4 stages, starting from socialization to program sustainability. The target partners of this activity are teachers in two elementary schools in Boyolali District. The results of this activity were that 15 participants managed to develop teaching modules independently. In addition, teachers' understanding of the concept of pedagogy and innovative learning models in target partners also increased to 81%